2016
DOI: 10.1097/01.aoa.0000482630.80689.e9
|View full text |Cite
|
Sign up to set email alerts
|

Is Fetal Cerebroplacental Ratio an Independent Predictor of Intrapartum Fetal Compromise and Neonatal Unit Admission?

Abstract: Topics: Neonatal Morbidity and Mortality, Systems-based Practice I dentifying whether a fetus is at risk for intrapartum hypoxia and other adverse conditions is challenging. Although smaller fetal size is more strongly associated with nonreassuring fetal status, many appropriate weight babies are also at risk for conditions such as cerebral palsy. A recent study suggested that fetal cerebroplacental ratio (CPR) measured within 72 hours of delivery, can successfully identify patients that will require obstetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
152
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(173 citation statements)
references
References 0 publications
18
152
2
1
Order By: Relevance
“…However, the CPR improves the prediction of adverse pregnancy outcomes when compared to its individual components [49][50][51][52][53]. It has been shown that a suboptimal or low CPR is associated with short-term markers of neonatal outcome such as cord blood acidemia, need for emergency operative delivery and neonatal unit admission [54][55][56][57], as well as stillbirth and neonatal morbidity [48,[57][58][59].…”
Section: Fetal Dopplermentioning
confidence: 99%
See 1 more Smart Citation
“…However, the CPR improves the prediction of adverse pregnancy outcomes when compared to its individual components [49][50][51][52][53]. It has been shown that a suboptimal or low CPR is associated with short-term markers of neonatal outcome such as cord blood acidemia, need for emergency operative delivery and neonatal unit admission [54][55][56][57], as well as stillbirth and neonatal morbidity [48,[57][58][59].…”
Section: Fetal Dopplermentioning
confidence: 99%
“…We recently reported that the CPR is a marker of failure to reach growth potential and adverse pregnancy outcomes, in both AGA and SGA fetuses [55,56], and this has been discussed in a recent review [63]. Most studies that assessed the utility of CPR in identifying at risk fetuses used point estimates and lacked longitudinal data.…”
Section: Fetal Dopplermentioning
confidence: 99%
“…CPR performed better in identifying fetuses with adverse outcome than the biophysical profile did [28]. Moreover, CPR was a better predictor for the birthweight centile regarding the necessity of admission to the neonatal intensive care unit [44]. These data encourage the recommendation of usage of CPR for risk stratification in L-IUGR fetuses [27].…”
Section: L-iugrmentioning
confidence: 68%
“…If in the third trimester, the obstetrician analyses only the UA PI, these fetuses will be missed and the potential intrapartum and postnatal complications cannot be anticipated [39]. An abnormal CPR and low birthweight centile were identified as significantly and independently associated with emergency caesarean section in both appropriate for gestational age (AGA) and L-IUGR groups [44]. CPR performed better in identifying fetuses with adverse outcome than the biophysical profile did [28].…”
Section: L-iugrmentioning
confidence: 99%
“…3,4 The implication of these findings is that fetuses do not have to be small to be hypoxaemic, and the finding of Murray et al is that not all small fetuses exhibit the long-term neurodevelopmental effects of hypoxaemia. Both of these statements have been long acknowledged as valid, but it is the recent finding of the influence of FCR (or CPR) that alludes to the fact that the mechanism involves prenatal uteroplacental insufficiency and fetal hypoxaemia.…”
Section: Sirmentioning
confidence: 99%